Bargaining over Governments in a Stochastic Environment - Merlo, Antonio (Journal of Political Economy, 1997)
In this paper, I structurally estimate a stochastic bargaining model of government formation in a multiparty parliamentary democracy, and I conduct policy experiments to evaluate the effects of changes in the bargaining procedure. I show that the model fits well data on the duration of negotiations and government durations in postwar Italy. Also, I show that changes in the proposer selection process would not affect either the duration of negotiations or government durations, whereas the imposition of a strict deadline would in general reduce the incentives to delay agreement as well as government durations.